F X Nottingham and F X Taunton Two Novel Mutations in Factor X Resulting in Loss of Functional Activity and an Interpretation Using Molecular Modelling - Deam, S.; Srinivasan, N.; Westby, J.; Horn, E.H.; Dolan, G. (Thrombosis and Haemostasis, 2001)
We report two novel mutations in the Factor X gene which result in a bleeding tendency in two unrelated Caucasian families. Although the mutations occur at adjacent codons in exon 8 and result in reduced functional activity with normal antigen levels, the patterns of inheritance appear to be quite distinct. Factor X Nottingham (alanine 404 threonine) appears to be associated with an autosomal recessive pattern of inheritance. In contrast, Factor X Taunton (arginine 405 glycine) results in a mode of inheritance consistent with an autosomal dominant pattern, all five of the heterozygotes in this family being clinically affected. Molecular modelling studies suggest that, in the case of Factor X Nottingham, a drastic conformational change causes major unfolding of the protein. For Factor X Taunton, less extreme conformational changes occur causing loss of functional activity such that substrate binding sites might be maintained. It is proposed that competition with wild type for substrate binding could occur leading to a dominant negative effect.
Keywords: Factor X mutations molecular modelling